Improving Solvolysis Rate Via Under Glass-Transition Temperatures Quenching Followed by Roll Bending of Carbon Fiber Reinforced Polymer Composite - Heru Sukanto; Bambang Kusharjanta; Mujtahid Kaavessina (TEKNIK, 2024)
Reusing carbon fiber once it has been used as reinforcement in composite structures involves a complex recycling technique. This recycling process requires a strategy to ensure the recycled carbon fiber meets technical standards. Among various recycling processes, the solvolysis technique yields carbon fiber with high purity. However, solvolysis is also the most time-consuming method. This study proposes using quenching and roll-bending pretreatments, which increase the contact surface area between the composite and the solvent solution for expediting the solvolysis process of carbon fiber reinforced polymer (CFRP) composite. Quenching was performed by heating the composite to 75°C, 100°C, and 125°C before immersing it in water at room temperature. Roll bending was designed based on the principle of three-point bending and aimed to induce a strain in the composite that exceeds the strain of the epoxy resin. Quenching at 75°C, followed by roll bending, resulted in a 21% increase in the surface area of the composite. This increased area improved the solvolysis efficiency of CFRP composites by up to 21% after four days of immersion in a mixture of acetone and acetic acid.